2016
DOI: 10.1002/jcu.22334
|View full text |Cite
|
Sign up to set email alerts
|

Carotid inter‐adventitial diameter is more strongly related to plaque score than lumen diameter: An automated tool for stroke analysis

Abstract: Our automated measurement system gave satisfying results in comparison with manual measurements. Carotid IAD was more strongly correlated to PS than carotid LD in this population sample of Japanese diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…The common carotid interadventitial diameter (IAD) can be easily measured as well as carotid IMT by using carotid ultrasonography. It is associated with vascular risk factors, carotid IMT, plaque scores, left ventricular mass, and myocardial infarction 26 , 101 103 ) . It was reported that the presence of both increased IAD, and increased IMT was the strongest predictor of stroke incidence in the general population 104 ) .…”
Section: Other Aspects Of Assessments Using Carotid Ultrasonographmentioning
confidence: 99%
“…The common carotid interadventitial diameter (IAD) can be easily measured as well as carotid IMT by using carotid ultrasonography. It is associated with vascular risk factors, carotid IMT, plaque scores, left ventricular mass, and myocardial infarction 26 , 101 103 ) . It was reported that the presence of both increased IAD, and increased IMT was the strongest predictor of stroke incidence in the general population 104 ) .…”
Section: Other Aspects Of Assessments Using Carotid Ultrasonographmentioning
confidence: 99%
“…Current systems are not fully automated 30 and lack advanced image-based features for risk assessment. 31,32 Often, these systems lack reliability, accuracy, reproducibility, and provide no comparative reference marker needed for monitoring. Furthermore, there is no standardization towards clinical trials.…”
Section: Introductionmentioning
confidence: 99%
“…Saba et al found that the correlation between AD and plaque score throughout the CCA, ICA, and bulb segments was 0.38 in a Japanese population. 54 The mechanisms affecting this measure of vascular remodeling during the menopause transition may be due to other factors such as endogenous hormones E2 and FSH, which dramatically change in the years surrounding the final menstrual period. 55 In the extended models in which we considered potential intermediate factors, we further adjusted for SBP, hsCRP, tPA, and PAI-1, and the effect size did not change appreciably.…”
Section: Discussionmentioning
confidence: 99%